Colon Cancer Reversed by Phyto-Nutritional Therapy: A Case Study - Yap, Steve (International Journal of Biotechnology for Wellness Industries, 2013)
Colorectal cancer is the second most common cancer in Malaysia and up to 80% of its patients seek complementary therapies. Globally, up to 95% of cancer patient use adjunct therapies to reduce chemotherapy-induced side-effects. Morgan et al. (2004) had showed that conventional treatment for colon cancer produced minimal results. The vast majority of cancer survivors admitted to using dietary supplements and herbs after their cancer diagnosis. Current treatment seems to pay more attention to cancer as a disease rather than meeting the physiological needs of the patient. Nutritional therapy should be individually tailored since dietary deficiency is multifactorial and the tumor burden for each patient is different. Cancer is a metabolic disorder and colon cancer is strongly associated with advancing age, dietary and lifestyle habits. Up to 90% of all cancers might be prevented with proper nutrition since one-third of overall cancer deaths are linked to malnutrition. This case study shows how a late stage colon adenocarcinoma might be completely reversed by evidence-based phyto-nutritional therapy combined with some lifestyle modifications. The cancer apoptotic properties of this natural protocol warrant further investigation involving a higher number of patients with similar conditions.